Why does water in porous carbon generate electricity? Electrokinetic role of protons in a water droplet-induced hydrovoltaic system of hydrophilic porous carbon. Issue 3 (5th January 2023) - Ko, Hyunseok; Son, Wonkyeong; Kang, Min Sung; Lee, Han Uk; Chung, Chan-Yeup; Han, Seungwu; Choi, Changsoon; Cho, Sung Beom
Abstract : The comprehensive multiphysics theoretical model on hydrovoltaics shows that the asymmetric protonation gradient and electrokinetic dynamics are the key factors for the mysterious electricity generation of porous carbons. Abstract : As emerging technology, hydrovoltaics harvests energy from water by flowing it through nanostructured materials. However, the poor understanding of the principles of hydrovoltaics has impeded its advancement. The process is complex and involves multiple simultaneous physico-chemical steps, and there has been extensive debate on aspects such as the streaming potential and ion flow. Herein, we report the first multiscale and multiphysics model for hydrovoltaic phenomena to provide in-depth interpretation and analysis of the working principles. Supported by experimental validation, this model explicitly considers the hydrodynamics in unsaturated porous media, ion transport, chemical reactions, and electrostatics. We found that protonation and ionic dynamics are the key factors for electricity generation. The difference in electric potential is mainly driven by the asymmetric proton concentration gradient, with a relatively small contribution from the streaming potential. Furthermore, the parametric effects of porosity, substrate geometry, catalytic activation energy, and room humidity were examined in detail. The results suggest a promising strategy to optimize the electrical performance of hydrovoltaic devices.